ANALISIS WEBSITE BAWASLU KOTAWARINGIN TIMUR MENGGUNAKAN COBIT 5 DENGAN DOMAIN EDM DAN MEA - winda pertiwi; Iik Eliyana Purnama Sari (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
The development of an increasingly rapid era makes information technology one of the most important parts of life. The use of information technology is widely used in various fields, one of which is government agencies. Government agencies that use information technology are BAWASLU. BAWASLU (General Election Supervisory Body) is one of the many government agencies in Indonesia. BAWASLU uses the website to provide information related to the ELECTION (General Election). One method that can be used to determine whether the Website has a standardized framework of information technology management practices is COBIT. The latest COBIT was released in 2012 with COBIT version 5. COBIT 5 (Control Objective for Information and related Technology) is a framework consisting of a best practice guide that contains information technology governance activities that focus on control and not on execution or implementation. Here the author chooses a domain based on the data sources that have been obtained. The domains used are EDM02, EDM05, and MEA01. Based on the results of research conducted on the BAWASLU website, EDM02 is at level 3 (Established Process), EDM05 is at level 2 (Managed Process), and MEA01 is at level 2 (Managed Process). With this method, the author can conclude that the current BAWASLU website has reached the stage.